The underground economy: an exploration of components, size, causes and effects - Amzuica, Bogdan; Mititelu, Roxana Adriana (Technium Social Sciences Journal, 2023)
The underground economy, which includes unlawful activities such as fraud, illegal labour, and crime, has received much attention because of its economic and social growth consequences. This article will analyze the underground economy’s components, size, causes, and impacts. The study employs comprehensive econometrics, statistical research, quantitative approaches, and real-world data from numerous countries. This study offers insight into the scale of the underground economy and its impact on society by examining descriptive statistics and doing cross-sectional studies. The underground economy is a vast and complex system encompassing various activities, from tax evasion and benefit fraud to counterfeiting and financial scams. It is estimated that the underground economy accounts for up to 30% of global GDP and can significantly impact economic growth, tax revenue, and public safety. The subsequent chapter examines the components of the underground economy, including fraudulent activities, counterfeit goods, and financial scams. It also discusses the challenges of detecting and preventing underground economic activity and the potential consequences of the underground economy for society. The paper calls for a more comprehensive approach to combating the underground economy, including measures to strengthen law enforcement, improve financial regulations, and educate the public about the risks of underground economic activity. This study investigated the relationship between the size of the population and the size of the underground economy in OECD countries. A quantitative research approach was used, and data were collected from secondary sources. The data were analyzed using SPSS software and EXCEL. The results showed a positive, linear relationship between the population and the underground economy. A stratified sampling method to collect data from OECD countries was used, where the data sources included government reports, tax records, academic research, and international databases. The data was analyzed using a simple linear regression model. The study concluded that there is enough evidence at a 95% confidence interval to suggest that the size of a country’s population is directly proportional to the size of its underground economy.